The Effectiveness of Critical Discourse-Based Writing Teaching Materials for Growing Student Nationalist Character in Higher Institutions - Supriadi Supriadi; Jufri Jufri; Sultan Sultan (Lembaga Sembilan Tiga Community, 2023)
This study aims to determine the effectiveness of writing teaching materials based on critical discourse for growing the character of student nationalism in higher institutions. This kind of research is development research. Sugiyono (2010: 407) states that development research is commonly called Research and Development (R&D), using the Thiagarajan 4-D development model. The teaching materials developed are writing teaching materials based on critical discourse to foster the character of student nationalism in higher institutions. Effectiveness data were obtained from students pre-test and post-test learning outcomes before and after using essential discourse-based writing materials in growing the character of nationalism in higher institutions. The data collection technique used to determine the effectiveness of teaching materials is to provide tests of students mastery of writing learning materials based on critical discourse. The analysis technique used is descriptive qualitative. Data on student learning outcomes analyzed by N-Gain showed an increase in students writing skills in higher institutions before and after treatment. The results of this study indicate that writing teaching materials based on critical discourse to growing the nationalism character of students in higher institutions is effectively implemented. The results are obtained based on the effectiveness test of teaching materials by conducting the N-Gain test. From the results of the N-Gain Score test, a score of 0.6 was brought based on dividing the N-Gain score category into the “medium” category with values ranging from 0.3 <g> 0.7. While the percentage value is 60%, based on the estimated percentage category N Gain is included in the “effective enough” category with a range of 56-75%.